Sustainable Support System for Rural Women Entrepreneurs : Ethiopia - Sawada, Naotaka; Harishchandra, Vedini (World Bank, Washington, DC, 2017)
Nonfarm sector development in rural Ethiopia is central to generating employment and income and thereby reducing poverty. The improved investment climate could facilitate investments in farm and nonfarm sectors by contributing directly and indirectly to the generation of additional employment for women and men. Ethiopia Industrial Development Strategy 2003 involved efforts to create an enabling environment for the private sector to be a driving force for economic development. The sectoral focus of the strategy is on the development of agro-based industries and on strengthening nonfarm sector. The sustainable support system for rural women entrepreneurs is based on five main components: (i) women's economic empowerment, (ii) market development, (iii) access to markets, (iv) business management support services, and (v) access to credit. Necessary conditions to support nonfarm economic activities, such as physical market development, feeder roads, and transport, will also benefit agriculture and create a virtuous circle of increasing farm and nonfarm income. Women are more likely to be involved in and benefit from nonfarm enterprise activities. Although the system proposed could be targeted at men and women, women could be the main beneficiaries of the support system. This sustainable system is new and innovative in directly supporting the rural poor and women by building the capacity of entrepreneurs and supporting institutions linked to the existing projects. This system may derive maximum synergy effects by integrating with the Agricultural Growth Project (AGP) and the Household Assets Building Program (HABP) of the Productive Safety Nets Project (PSNP) in a complementary relationship.